Ação de emulsões de óleos essenciais sobre endósporos de Clostridium botulinum e Clostridium sporogenes em mortadela sem adição de nitrito - Isidoro, Silas Rodrigo (2021)
Spice essential oils have stood out as a promising alternative, not only in substitution, but also in conjunction with reduced concentrations of synthetic preservatives in foods such as nitrite salts, for the control of various microorganisms. This work aimed to evaluate the antimicrobial action of a mixture of essential oils on endospores of Clostridium botulinum type A and Clostridium sporogenes inoculated in mortadella without the addition of nitrite as well as their influence on the physicochemical characteristics of the product. The minimum inhibitory concentrations (MIC) and minimum sporicidal concentrations (MSC) of the essential oils of garlic, basil, Chinese pepper, pink pepper, savory and thyme were determined using Reinforced Clostridium Broth (RCM) plus 0.5% (v/v) Tween 80, incubation at 37°C/48 hours under anaerobic conditions. All oils showed a MIC of 0.094% over C. botulinum, however, for C. sporogenes there were variations between 0.094 to 0.188% (v/v). Only garlic was sporicidal among the oil concentrations tested, with MSC of 1.5% (v/v) for C. botulinum and 3% (v/v) for C. sporogenes. From these results, garlic, savory, basil and pink pepper oils were selected for the study of synergism. Using the Central Rotational Composite Design (DCCR), 27 mixtures of the selected essential oils were prepared and evaluated for their inhibitory activity. The methodology used was the same as that used to determine MIC and MSC. All mixtures inhibited the growth of both bacteria, but none showed sporicidal action. Thus, the assay containing 0.019% garlic, 0.019% basil, 0.019% pink pepper and 0.019% savory was selected to evaluate the inhibitory action on C. botulinum and C. sporogenes inoculated in mortadella. These were inoculated with 104 CFU/g of bacterial endospores, added with essential oils and maintained at 15ºC/15 days. The quantification of the vegetative cells and endospores of C. botulinum and C. sporogenes was performed, as well as the determination of pH, lipid oxidation and color evaluation of mortadella, on days 0, 3, 6 and 15 days. C. botulinum showed greater sensitivity when compared to C. sporogenes to essential oils. During the storage period, it was observed that both C. botulinum and C. sporogenes spores germinated and multiplied, however, the vegetative cells of C. botulinum remained practically stable and slightly decreased over time, whereas those of C. sporogenes increased rapidly. The emulsion of the oils reduces the lipid oxidation of the product, does not alter the pH and promotes changes only in the luminosity (L*), making the product darker. It can be concluded that the two strains behave differently when subjected to the presence of essential oils in a meat product and that the emulsion of the essential oils tested proved to be promising as a preservative and antioxidant to be used in meat products to replace nitrite salts.